Measurement of the D/H, (18)O/(16)O, and (17)O/(16)O Isotope Ratios in Water by Laser Absorption Spectroscopy at 2.73 μm - Wu, Tao (Molecular Diversity Preservation International (MDPI), 2014)
A compact isotope ratio laser spectrometry (IRLS) instrument was developed for simultaneous measurements of the D/H, (18)O/(16)O and (17)O/(16)O isotope ratios in water by laser absorption spectroscopy at 2.73 μm. Special attention is paid to the spectral data processing and implementation of a Kalman adaptive filtering to improve the measurement precision. Reduction of up to 3-fold in standard deviation in isotope ratio determination was obtained by the use of a Fourier filtering to remove undulation structure from spectrum baseline. Application of Kalman filtering enables isotope ratio measurement at 1 s time intervals with a precision (<1‰) better than that obtained by conventional 30 s averaging, while maintaining a fast system response. The implementation of the filter is described in detail and its effects on the accuracy and the precision of the isotope ratio measurements are investigated.